Simultaneous exposure to MRI‐related static and low‐frequency movement‐induced time‐varying magnetic fields affects neurocognitive performance: A double‐blind randomized crossover study. Issue 3 (15th September 2014) - van Nierop, Lotte E.; Slottje, Pauline; van Zandvoort, Martine; Kromhout, Hans
<x xml:space="preserve">Abstract</x> Purpose This experimental study aims to separate neurocognitive effects resulting from exposure to static magnetic stray fields (SMF) alone and the combination of SMF and low‐frequency movement‐induced time‐varying magnetic fields (TVMF) using a 7 Tesla (T) MRI scanner in stand‐by mode. Methods In a double‐blind randomized crossover experiment, 36 healthy volunteers underwent four sessions, two exposed conditions, and two corresponding sham conditions. The exposure conditions were in front of the scanner bore and consisted of 1.0 T SMF with or without 2.4 T/s TVMF, induced by standardized head movements before each of the five neurocognitive tasks. These specific tasks were selected because previous experiments showed negative effects of SMF + TVMF exposure on test performance. Results Exposure to SMF in combination with TVMF decreased verbal memory performance significantly and changed visual acuity. Similarly, attention and concentration were negatively affected with borderline significance. Exposure to SMF only did not have significant effects on the performance on any of the tasks. Conclusion Neurocognitive effects were only observed when simultaneously exposed to SMF and TVMF from a 7 T MRI scanner. Therefore, exposure to TVMF seems essential in eliciting the neurocognitive effects in our present study and, presumably, previous experiments. Magn Reson Med 74:840–849, 2015. © 2014 Wiley Periodicals, Inc.